Moderasi Beragama Suatu Langkah Menjaga Kebhinekaan - Pinondang Simanjuntak (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The differences that the Indonesian state has are often used as the basis for conflicts that occur within this country. The diversity of religions, ethnicities, races, cultures and traditions that exist often differentiates Indonesian society. These differences often become the root of a problem and ultimately result in unrest and lack of harmony in social life. In this regard, in maintaining the values ​​of diversity, the Ministry of Religion provides religious moderation to handle any differences that occur. The Ministry of Religion never tires of promoting Religious Moderation, because with this, peace, tranquility and an attitude of tolerance between communities can be realized. Maintaining the value of diversity is not an easy thing, nowadays there are often divisions between communities, discrimination between communities, groupings between tribes, this is what is trying to be resolved with the existence of Religious Moderation. Maintaining diversity is not only the task of government institutions, but all members of society play a role and are responsible for this. Therefore, by promoting religious moderation, this will be the most effective way to overcome the widespread intolerance. Religious moderation will also make people aware of the importance of the value of togetherness among differences. This will look for the most appropriate way to cultivate existing diversity, making it a wealth that cannot be valued.